PENGARUH FASILITAS DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI WARUNG AYAM BAKAR MBAK LIS SAWANGAN DEPOK - Zahra Tunnisa; F Budi Syamtoro (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract.  This study aims to analyze the influence of facilities and packaging design on consumer purchasing decisions at Mbak Lis grilled chicken stall. The background of this research is the importance of facilities and packaging design in facing the intense competition in the culinary business, especially for Micro, Small, and Medium Enterprises (MSMEs). The results show that facilities have a significant effect on consumers' purchasing decisions, proven by a significance value of (0.000) < (0.05) and a t count (8.347) > t table (0.1984). Similarly, packaging design also has a significant effect on consumers' purchasing decisions, with a significance value of (0.000) < (0.05) and a t count (8.014) > t table (0.1984). Furthermore, simultaneously, facilities and packaging design positively and significantly influence consumers' purchasing decisions, supported by an F test with F count (49.055) > F table (3.941) and a significance value (0.000) < (0.05). These findings confirm that the regression model can be used to predict consumers' purchasing decisions.